Development of an Integrated Grass-Cutting SOP Based on Permit to Work and API 500/505 Standards for Improving OHS System Reliability - Elen Sahan Wijaya; Felixtianus Eko Wismo Winarto (Rifa'Institute, 2026)
Introduction: Grass-cutting activities in upstream oil and gas facilities present significant safety risks, particularly in hazardous classified areas. Previous incidents revealed inadequate integration between the Permit to Work (PTW) system and API 500/505 hazardous area classification standards, resulting in insufficient hazard control Objective: To develop and evaluate an integrated Standard Operating Procedure (SOP) combining PTW requirements with API 500/505 standards to improve OHS system reliability Method: An action research design with mixed-methods approach was conducted at PT XYZ Oil & Gas Indonesia, drawing on 141 maintenance-related incidents (2019–2024) and validated through a five-month pilot implementation Results and Discussion: Baseline assessment revealed weaknesses in PTW compliance (67%), permit quality (58%), hazard identification (45%), and personnel competency (50.9%). Following SOP implementation, competency increased significantly to 80.4% (t=23.330; p<0.05), with N-Gain of 0.602 and 88.9% of participants achieving competency targets. The intervention demonstrated a very large practical effect (Cohen's d≈7.78). Conclusion: The integrated SOP effectively improved personnel competency and strengthened OHS system reliability, providing a practical approach to safer grass-cutting operations in upstream oil and gas facilities